Methodology of identification of the drainage norm for areasexposed to flooding МЕТОДОЛОГИЯ ОПРЕДЕЛЕНИЯ НОРМЫ ОСУШЕНИЯ НА ПОДТАПЛИВАЕМЫХ ТЕРРИТОРИЯХ - Voronov Yuriy Viktorovich (Vestnik MGSU, 2013)
The authors argue that drainage norms depending on the functional use of territories must be considered as the first step in the design of flood protection systems. Further, calculation of the drainage norm should be performed based on the extent of the flooding vulnerability of areas. Any designer should identify the parameters of hazards that may cause harmful effects, including the groundwater level, the moisture content of soil, contamination of the groundwater and soil, and the change of soil properties by soaking and draining in order to characterize the hazard of flooding processes in urban and industrial areas. The classification of factors affecting the vulnerability of urban and industrial areas is based on the four features, or indicators of vulnerability, including urban, geotechnical, environmental, and operational indicators. An assessment of harmful effects of flooding should be made following the identification of the flooding hazard degree and the vulnerability of the area to flooding. The research findings contain the threshold of the geological safety and the acceptable depth of the groundwater. Any design of engineering protection actions should take account of the drainage norm within the boundaries based on the acceptable groundwater level in terms of the geological safety threshold. Производится расчет нормы осушения территории в зависимости от степени опасности подтопления и от степени уязвимости территории. Определяются показатели опасности, которые вызывают те или иные виды вредного воздействия. Проводится классификация факторов, влияющих на уязвимость градопромышленных территорий, по четырем признакам, которые называются показателями уязвимости. После проведения исследований по определению уровня опасности развивающихся на данной территории процессов подтопления и уровня уязвимости этой территории вследствие ее подтопления производится оценка вредного воздействия подтопления градопромышленной территории. Определен порог геологической безопасности и допустимой глубины грунтовых вод.